(untitled) (Research, Society and Development, 2021)
The newly discovered SARS-CoV-2 virus quickly spread worryingly from China around the world causing what experts call the biggest pandemic of the century, causing hospital overcrowding, millions of deaths and immeasurable damage to public health. In order for students not to be harmed even more and teaching in the country to suffer unprecedented negative impacts in the short and long term, the face-to-face teaching institutions had to adapt and reinvent the way they offer classes even with the imposition of social distancing. Therefore, most schools opted for emergency remote teaching, a modality that required quick training courses to better prepare the teacher for the moment experienced, especially in relation to the use of digital media, which became the main tools for planning, elaboration and realization of remote classes in the public school system. That said, this work sought to know and analyze the main adversities presented by teachers of a public school in the state network of the city of Pedro Afonso against the use of digital media employed in remote teaching, in order to obtain a sample of what possibly many teachers by country have also faced in this scenario. For this, online questionnaires were applied to the teachers of the School Unit, which allowed, from the collection and analysis of data, to highlight the lack of preparation that many showed regarding the use of media, even with brief training aimed at the current scenario.